Środowisko przyrodnicze i procesy gospodarowania w ujęciu doktryny New Age - Becla, Agnieszka; Czaja, Stanisław (Environment and Economy Processes in the New Age Doctrine, 2005)
In article has presented means of nature interpretation in the science and philosophy. It has presented a basic elements of New Age and role of nature, too. Last part of article included short presentation of new economy and new society (D. Korten model's) in New Age doctrine.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 22-35